Mechanical properties of steel reinforced concrete T-shaped column after high temperature. (December 2022) - Wang, Yuzhuo; Gong, Junlin; Qu, Shuang; Zhang, Bingjie; Chen, Yangting
Abstract: The mechanical properties of 9 steel reinforced concrete T -shaped column specimens after high temperature were studied in this paper. The investigated factors included high temperature duration, loading eccentricity, loading angle and steel content. The test results showed that: (1) The failure mode of axial compression specimen was shear failure, and eccentric compression specimen was bending failure. (2) The stiffness of the specimen decreased with the increase of high temperature duration, loading eccentricity, loading angle and the decrease of steel content. (3) The ductility was quantitatively analyzed, and loading eccentricity and steel content had a more significant influence on the ductility than high temperature duration and loading angle. (4) With the increase of high temperature duration, loading eccentricity, loading angle and the decrease of steel content, the bearing capacity was reduced by 15.63 % ∼ 24.65 %, 8.87 % ∼ 14.76 %, 3.17 % ∼ 5.16 % and 18.71 % respectively. Finally, the simplified bearing capacity calculation method of steel reinforced concrete T-shaped column after high temperature was put forward, which provided a reference for post-disaster structural evaluation and reinforcement.